2021
DOI: 10.2298/ntrp210112014h
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclides’ content in forest ecosystem located in southwestern part of Serbia

Abstract: Forests, with a large coverage of lands area, represent important ecosystem. They have greater ability to absorb atmospheric pollutant, including radionuclides compared to other vegetation types. Thus it is important to monitor radionuclides concentration in forest ecosystems. The results of the first gamma-spectrometric measurements in 16500 ha large region of South-western Serbia are presented. It is investigated activity concentrations of 40K, 137Cs and 210Pb in different deciduous and eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…In another study examining the medicinal plants used in traditional medicine in Thailand, the mean 40K activity concentration was found to be 610±260 Bq kg -1 and TF value to be 2.0±1.4 and it was determined that the activity concentration was at a higher level in leaves in comparison to flowers and stem Saenboonruang et al [7]. In their study carried out on forests in Southwestern Serbia region, Hadrovıć et al [34] reported the 40K activity concentration of evergreen species to be 102 ± 25 Bq kg -1 , that of non-evergreen species to be 140 ± 26 Bq kg -1 , and that of samples from the soil, where the plants were grown, to be 62±5-970±60 Bq kg -1 . TF (40K) was found to be 0.022-0.22 in non-evergreen species and 0.007-0.19 in coniferous species.…”
Section: K Activity Concentration Changes In Plants Treated With CD A...mentioning
confidence: 97%
See 2 more Smart Citations
“…In another study examining the medicinal plants used in traditional medicine in Thailand, the mean 40K activity concentration was found to be 610±260 Bq kg -1 and TF value to be 2.0±1.4 and it was determined that the activity concentration was at a higher level in leaves in comparison to flowers and stem Saenboonruang et al [7]. In their study carried out on forests in Southwestern Serbia region, Hadrovıć et al [34] reported the 40K activity concentration of evergreen species to be 102 ± 25 Bq kg -1 , that of non-evergreen species to be 140 ± 26 Bq kg -1 , and that of samples from the soil, where the plants were grown, to be 62±5-970±60 Bq kg -1 . TF (40K) was found to be 0.022-0.22 in non-evergreen species and 0.007-0.19 in coniferous species.…”
Section: K Activity Concentration Changes In Plants Treated With CD A...mentioning
confidence: 97%
“…137Cs activity concentrations in soil and grass in Bangladesh were reported to be 0.17 ± 0.02 Bq kg -1 and 2.41 ± 0.18 Bq kg -1 , respectively, whereas TF value was found to be 0.061 [31]. Shayeb et al [34] compaJapanaesethe 137Cs activity concentrations in date and soil samples collected from different regions of Saudi Arabia and they reported the activity in soil to be 10.2 ± 2.1 Bq kg -1 and the activity in date samples to be below the limit of detector. In a study carried out using tea leaves, 137Cs activity concentration was found to be <0.4 Bq kg -1 in the leaves and 3±1-10±1 Bq kg -1 in the soils, whereas TF (137Cs) was found to be belwo the limit of detector [4].…”
Section: Cs Activity Concentration Changes In Plants Treated With CD ...mentioning
confidence: 99%
See 1 more Smart Citation
“…where A Ei rep re sents the ab sorp tion of the i th radionuclide via the soil-plant path way by dry veg e ta ble weight from dry soil weight [17].…”
Section: De Ter MI Na Tion Of Soil-to-veg E Ta Bles Trans Fer Fac Torsmentioning
confidence: 99%
“…The ac tiv ity con centra tion of 40 K was di rectly an a lyzed us ing the gamma-ray line at 1461 keV (10.7 %) rep re sented in tab. 1 [5,6]…”
Section: Mea Sure Ment Of Ra Dio Ac Tiv Itymentioning
confidence: 99%